Fostering Harmony through Islamic Communication: A Case Study of FKUB Medan City - Purba, Anggi Martuah; Mukhtaruddin, Mukhtaruddin (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2024)
This study examines applying the Forum Kerukunan Umat Beragama (FKUB) in Medan City to maintain harmony between religious communities. FKUB plays an important role in enforcing policies and technical guidelines in interfaith peace. Using Jalaluddin Rakhmat's theoretical approach, this study explores how Islamic communication principles help maintain harmony and transform differences of opinion into friendship in Medan. This study uses a qualitative case study method with data collection techniques through documentation, interviews, and observations. Documentation includes analysis of official documents and reports of FKUB activities. Interviews were conducted with FKUB members and administrators to gain in-depth insight into the communication strategies they use. Direct observation of FKUB activities was conducted to see the dynamics of interactions between religious communities. The results of the study show that FKUB upholds two main principles of Islamic communication: Qaulan Syadidan (true and appropriate words) and Qaulam Ma'rufa (good words). Qaulan Syadidan ensures communication-based on honesty and accuracy, while Qaulam Ma'rufa encourages the use of polite and good language. These two principles have proven effective in creating constructive and harmonious dialogue in the diverse society of Medan City.